Method for improving structural stability of layered lithium-rich manganese-based oxide positive electrode material for lithium ion battery
By introducing lanthanum ion structure pinned LaNiO3 into the layered lithium-rich manganese-based oxide positive electrode material, the problems of structural instability and interface corrosion of the material during the charge and discharge cycle are solved, and electrochemical performance and cycle stability are improved. The commercial application of high-energy density lithium-ion batteries has been realized.
Patent Information
- Application Number
- CN202411034416.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-31
AI Technical Summary
Layered lithium-rich manganese-based oxide positive electrode materials have structural instability and interface corrosion problems during the charge and discharge cycle, resulting in a decrease in energy density and poor cycle stability.
By introducing lanthanum ions, the pinned phase LaNiO3 is constructed to inhibit the lattice parameter expansion of LiMn1/3Ni1/3Co1/3O2 nanodomain, and a lanthanum modified lithium-rich manganese-based oxide positive electrode material is obtained through two-step heat treatment and vacuum drying, thereby improving the material structural stability.
Significantly improves electrochemical performance, including initial Coulomb efficiency and capacity/voltage cycling stability, simplifying the preparation process and reducing costs.
Smart Images

Figure CN119191377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of lithium ion battery electrode materials, and specifically relates to a preparation method of a lanthanum ion modified lithium-rich manganese-based oxide positive electrode material and its application in lithium ion battery positive electrode materials. Background Art
[0002] The decreasing global fossil energy and the rapid growth of society's demand for energy have forced people to focus on new energy sources such as clean wind energy, hydropower, and solar energy. The development of such new energy sources, which are affected by time, environment, and geographical factors, has prompted the development of energy storage technology. Lithium-ion batteries have attracted widespread attention due to their advantages such as high energy density, low self-discharge, no memory effect, and wide operating temperature range. As an important component of lithium-ion batteries, the performance, cost, and safety of positive electrode materials directly determine the commercial application of lithium-ion batteries. At present, the more mature positive electrode materials are lithium iron phosphate and lithium cobalt oxide, and the new LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The research on O2 ternary positive electrode materials is also becoming more mature. However, compared with the mature graphite negative electrode (372mAh g -1 ) compared to the existing cathode materials, the capacity is mostly less than 200 mAh g -1 , which seriously limits the further improvement of the energy density of lithium-ion batteries.
[0003] Layered lithium-rich manganese-based oxides have high discharge capacity and working voltage, and their energy density can reach nearly 1000Wh kg -1 , and its low price and high safety make it considered to be a very promising cathode material for the next generation of lithium-ion batteries. 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2) positive electrode material is LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 O2 (space group is R-3m) and Li2MnO3 (space group is C2 / m) two nanodomains, and these two nanodomains have different redox activities. During the charging process, when the charging voltage is lower than 4.4V, Li is mainly released from the R-3m nanodomain. + ions, while the C2 / m nanodomains basically do not evolve. +After the ions are deposited, the Coulomb repulsion of the lattice oxygen causes its lattice parameters to expand (mainly concentrated on the lattice parameter c), while the lattice parameters of the C2 / m nanodomain remain unchanged. The two continuous nanodomains undergo lattice mismatching, resulting in the accumulation of stress and strain, which in turn exacerbates the lattice oxygen loss and layered structure phase transition under high voltage. The lattice oxygen precipitated under high voltage is very likely to react with the electrolyte to generate acidic substances, corrode the interface of the positive electrode material, and continuously dissolve the transition metal elements, resulting in poor interface stability of the lithium-rich manganese-based oxide material. Poor interface stability and structural stability aggravate the attenuation of the discharge specific capacity and discharge voltage of the lithium-rich manganese-based oxide positive electrode during the charge and discharge cycle, resulting in a continuous decrease in energy density and poor cycle stability.
[0004] Patents with publication numbers CN114864908A, CN103441252A and CN103928664B respectively use corrosion-resistant fluorides, oxides, phosphates and other materials to coat layered lithium-rich manganese-based oxide positive electrode particles. Although this modification method effectively alleviates the corrosion of the electrolyte to the positive electrode material and the appropriate coating layer can increase the interface transmission rate of lithium ions / electrons, it does not have a significant inhibitory effect on the structural transformation problem, and in long-term charge and discharge cycles, the rigid coating layer is difficult to completely and tightly coat the layered lithium-rich manganese-based oxide positive electrode particles with volume changes, causing the coating layer to gradually fail. Lattice doping has also been widely studied as a modification method that can effectively stabilize the structure.
[0005] Patents with publication numbers CN113540458A and CN112599765A respectively use ions larger than Li + Alkali metal ions (Na + , K + ) replaces Li + Or the patents with publication numbers CN111987297A and CN113224290A are respectively 3+ 、Ti 4+ Plasma partially replaces transition metal ions, relying on increasing the energy barrier that transition metal ions cannot migrate to improve the stability of the layered structure, and Na + , K + The large-sized ions enlarge the interlayer spacing of the Li layer, promoting the + However, traditional coating and doping are difficult to solve the problem of different redox characteristics of the two nanodomains, and it is difficult to suppress the mismatch of lattice parameters between R-3m and C2 / m nanodomains during charging. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for improving the structural stability of layered lithium-rich manganese-based oxide positive electrode materials for lithium-ion batteries.
[0007] In order to solve the above problems, the present invention provides a method for preparing a lanthanum-modified lithium-rich manganese-based oxide positive electrode material, comprising the following steps:
[0008] S1. Add nickel ion salt, cobalt ion salt, manganese ion salt, lithium ion salt and lanthanum ion salt to deionized water, and stir at room temperature until completely dissolved to obtain a mixed salt solution;
[0009] Nickel ion: cobalt ion: manganese ion: lithium ion = 0.13: 0.12-0.14: 0.53-0.55: (1.15-1.25) × 1.05 molar ratio;
[0010] The sum of nickel ions, cobalt ions and manganese ions is named transition metal ions, and the molar ratio of transition metal ions: lanthanum ions is 100-x:x, wherein x is 0.1 to 10 (preferably 1 to 10);
[0011] The sum of nickel ions, cobalt ions, manganese ions, lithium ions, and lanthanum ions is named as total metal ions;
[0012] S2, adding citric acid and ethylene glycol to the mixed salt solution obtained in S1, and uniformly mixing and stirring at room temperature until the citric acid is completely dissolved;
[0013] The molar ratio of total metal ions: citric acid: ethylene glycol is 1: 0.1-5: 0.1-5 (preferably 1: 1.4-1.6: 1.4-1.6);
[0014] S3, placing the solution obtained in S2 in a water bath, and keeping it in a water bath at 60-90°C for 6-24 hours;
[0015] S4, placing the product obtained in S3 in a vacuum drying oven for constant temperature vacuum drying to obtain a foam precursor;
[0016] S5. Under air atmosphere, the foam precursor obtained in S4 is subjected to two-step heat treatment in sections to obtain a lanthanum-modified lithium-rich manganese-based oxide positive electrode material.
[0017] As an improvement of the preparation method of the lanthanum-modified lithium-rich manganese-based oxide positive electrode material of the present invention:
[0018] The nickel ion salt, cobalt ion salt, manganese ion salt, lithium ion salt and lanthanum ion salt may be any of the following: nitrate, sulfate, acetate and chloride.
[0019] As a further improvement of the method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material of the present invention, in step S5:
[0020] The first step of heat treatment is at a temperature of 300 to 700°C, a heating rate of 1 to 7°C / min, and the heat treatment is continued at this temperature for 4.5 to 24 hours;
[0021] The second step heat treatment temperature is 700-1000°C, the heating rate is 1-7°C / min, and the heat treatment is continued at this temperature for 6-24 hours.
[0022] As a further improvement of the method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material of the present invention, in step S4:
[0023] The vacuum drying temperature is 100 to 300° C., and the vacuum drying time is 6 to 24 hours.
[0024] As a further improvement of the preparation method of the lanthanum-modified lithium-rich manganese-based oxide positive electrode material of the present invention:
[0025] In step S1:
[0026] The molar ratio of nickel ion: cobalt ion: manganese ion: lithium ion = 0.13: 0.13: 0.54: (1.2 × 1.05);
[0027] (nickel ion + cobalt ion + manganese ion): lanthanum ion = 99:1 molar ratio;
[0028] In step S2:
[0029] (nickel ion + cobalt ion + manganese ion + lithium ion + lanthanum ion): citric acid: ethylene glycol = 1:1.5:1.5 molar ratio;
[0030] In step S5:
[0031] The first step of heat treatment is at a temperature of 500±20°C, a heating rate of 5±0.1°C / min, and the heat treatment is continued at this temperature for 5±0.1 hours;
[0032] The second step heat treatment temperature is 900±20°C, the heating rate is 5±0.1°C / min, and the heat treatment is continued at this temperature for 12±0.1 hours.
[0033] The present invention also provides a method for improving the structural stability of layered lithium-rich manganese-based oxide positive electrode materials for lithium-ion batteries: the material obtained by any of the above methods is used as a positive electrode material for lithium-ion batteries.
[0034] High energy density is a well-known feature of lithium-rich manganese-based oxide cathode materials, but the structural stability of such high energy density cathode materials is relatively poor, which directly leads to a decrease in electrochemical performance. Based on the above research, the present invention introduces lanthanum ions into LiMn 1 / 3 Ni 1 / 3 Co 1 / 3 The perovskite phase LaNiO3 is constructed in O2 nanodomains as a pinning phase, and the pinning effect of LaNiO3 is used to suppress the LiMn 1 / 3 Ni 1 / 3 Co1 / 3 The lattice parameters of O2 nanodomains expand during the low-voltage delithiation process, and the electrochemical and thermodynamic stability of LaNiO3 also ensure its durability and reliability as a pinning phase. The lattice mismatch problem between continuous nanodomains is improved, which alleviates the accumulation of stress and strain, thereby inhibiting the lattice oxygen loss and layered structure phase transition under high voltage, thereby achieving structural stability. The electrochemical properties of the structurally stable positive electrode material, such as the initial coulombic efficiency and capacity / voltage cycle stability, are greatly improved, and this synthesis method is simple and controllable, which can effectively promote the commercial application of layered lithium-rich manganese-based oxide positive electrode materials in high energy density lithium-ion batteries.
[0035] That is, the present invention generates a new phase by adding La to stabilize the structure, thereby improving the electrochemical performance.
[0036] The present invention has the advantages of simple and controllable preparation process, low cost and excellent electrochemical performance. In the preparation process (which can adopt the sol-gel method), lanthanum salt is additionally added to obtain a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material with outstanding cycle stability, and the initial coulombic efficiency and capacity / voltage cycle stability are improved.
[0037] The present invention has the following beneficial effects:
[0038] 1. The process of the present invention is simple and controllable, low in cost, and has excellent electrochemical performance;
[0039] 2. Relying on the "pinning" effect of the pinning phase constructed by lanthanum ions in the structure of the positive electrode material, the stability of the layered structure of the lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material is significantly improved;
[0040] 3. When used as the positive electrode of lithium-ion batteries, the initial coulombic efficiency and capacity / voltage cycling stability are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0042] Figure 1 This is the X-ray diffraction pattern of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0043] Figure 2 This is a scanning electron microscope image of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0044] Figure 3 This is a low-magnification transmission electron microscope image of the lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0045] Figure 4This is a high-magnification transmission electron microscope image of the lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0046] Figure 5 This is the first cycle charge and discharge curve of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0047] Figure 6 The discharge specific capacity cycle stability of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0048] Figure 7 It is the average discharge voltage cycle stability of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 1.
[0049] Figure 8 This is the X-ray diffraction pattern of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 2.
[0050] Fig. 9 This is the first cycle charge and discharge curve of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 2.
[0051] Fig.10 The discharge specific capacity cycle stability of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 2.
[0052] Fig.11 It is the average discharge voltage cycle stability of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material prepared in Example 2.
[0053] Fig.12 This is the X-ray diffraction pattern of the unmodified lithium-rich manganese-based oxide positive electrode material prepared in Example 3.
[0054] Fig.13 This is the first cycle charge and discharge curve of the unmodified lithium-rich manganese-based oxide positive electrode material prepared in Example 3.
[0055] Fig.14 The discharge specific capacity cycle stability of the unmodified lithium-rich manganese-based oxide positive electrode material prepared in Example 3.
[0056] Fig.15 It is the average discharge voltage cycle stability of the unmodified lithium-rich manganese-based oxide positive electrode material prepared in Example 3. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0058] Note: Since Li will volatilize during high-temperature sintering, an additional 5wt% will be added on the basis of stoichiometric amount to compensate for the volatilized Li. This is a common requirement in this industry.
[0059] Example 1: A method for preparing a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material (a method for improving the structural stability of a layered lithium-rich manganese-based oxide positive electrode material for a lithium-ion battery), comprising the following steps:
[0060] 1) Add 0.009780 mol nickel nitrate hexahydrate, 0.009780 mol cobalt nitrate hexahydrate, 0.040625 mol manganese nitrate (50 wt% deionized water solution), and 0.094792 mol lithium nitrate (5 wt% excess) to 100 ml of deionized water, and stir at room temperature until completely dissolved;
[0061] Therefore, the molar ratio of nickel ion: cobalt ion: manganese ion: lithium ion = 0.13: 0.13: 0.54: (1.2 × 1.05);
[0062] Then add 0.000608 mol of lanthanum nitrate hexahydrate and stir at room temperature until the lanthanum nitrate hexahydrate is completely dissolved to obtain a transparent and clear mixed salt solution;
[0063] Therefore, the molar ratio of (nickel ion+cobalt ion+manganese ion):lanthanum ion=99:1.
[0064] 2) Add 0.2333775 mol of citric acid and 0.2333775 mol of ethylene glycol to the mixed salt solution obtained in step 1), and mix and stir evenly at room temperature until the citric acid is completely dissolved;
[0065] Therefore, the molar ratio of (nickel ion + cobalt ion + manganese ion + lithium ion + lanthanum ion): citric acid: ethylene glycol = 1:1.5:1.5.
[0066] 3) Place the solution obtained in step 2) in a water bath at 80° C. for 8 hours (evaporation to dryness is also performed accordingly during the water bath process);
[0067] 4) placing the product obtained in step 3) in a vacuum drying oven and drying it at 200° C. (vacuum degree of -0.1 MPa) for 8 hours to obtain a foam precursor;
[0068] 5) In an air atmosphere, the foam precursor is first heated to 500°C at a rate of 5°C / min and kept at this temperature for 5 hours, and then heated to 900°C at a rate of 5°C / min and kept at this temperature for 12 hours to obtain a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material.
[0069] The X-ray diffraction pattern of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material obtained in Example 1 is as follows: Figure 1 Scanning electron microscope images are shown in Figure 2 As shown, the low-magnification image and high-magnification image of the transmission electron microscope are shown in Figure 3 and Figure 4 As shown. Figure 1 to Figure 4 , we can know that: X-ray diffraction peaks show typical lithium-rich manganese-based oxide structural characteristics, and low-magnification electron microscopy shows a granular morphology with uniform size. High-magnification transmission electron microscopy images show a new LaNiO3 structure that grows coherently with the layered lithium-rich manganese-based oxide positive electrode. Figure 4 From the transmission electron microscope photograph, we can see that the atoms are arranged in layers.
[0070] Experiment 1: The material obtained in Example 1 was applied to the positive electrode material of lithium-ion batteries. The temperature of the environmental simulation device was set to 25°C. The battery was left standing at 25°C for 12 hours, charged to 4.8V at a constant current density, left standing for 5 minutes, and discharged to 2.0V at a constant current density. The results were as follows:
[0071] 20mA g -1 At this current density, the initial Coulomb efficiency in the first cycle of activation charge and discharge can reach 91.15%. -1 At the current density, after 200 cycles, the discharge capacity retention rate was 96.36%, and the average discharge voltage retention rate was 90.56%. Figure 5 to Figure 7 shown.
[0072] Example 2: A method for preparing a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material, comprising the following steps:
[0073] 1) The amount of lanthanum nitrate hexahydrate in step 1) of Example 1 was changed from 0.000608 mol to 0.001861 mol, so that the molar ratio of (nickel ion + cobalt ion + manganese ion): lanthanum ion = 97:3;
[0074] The rest is the same as step 1) of Example 1.
[0075] 2) Add 0.235257 mol of citric acid and 0.235257 mol of ethylene glycol to the mixed salt solution obtained in step 1), and mix and stir evenly at room temperature until the citric acid is completely dissolved;
[0076] Therefore, the molar ratio of (nickel ion + cobalt ion + manganese ion + lithium ion + lanthanum ion): citric acid: ethylene glycol = 1:1.5:1.5.
[0077] Step 3) to Step 5) are equivalent to Step 3) to Step 5) of Example 1.
[0078] The X-ray diffraction pattern of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material obtained in Example 2 is as follows: Figure 8 shown.
[0079] According to the same detection method as in Example 1, the results obtained are: at 20 mA g -1 The first cycle activation coulombic efficiency at current density is 87.62% at 100mAg -1 At the current density, after 200 cycles, the discharge capacity retention rate was 86.70%, and the average discharge voltage retention rate was 89.73%. Figures 9 to 11 shown.
[0080] Example 3: A method for preparing a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material, comprising the following steps:
[0081] 1) The use of lanthanum nitrate hexahydrate is eliminated, that is, the amount of lanthanum ions used is 0; the rest is equivalent to step 1) of Example 1.
[0082] 2) Add 0.2324655 mol of citric acid and 0.2324655 mol of ethylene glycol to the mixed salt solution obtained in step 1), and mix and stir evenly at room temperature until the citric acid is completely dissolved;
[0083] Therefore, the molar ratio of (nickel ion+cobalt ion+manganese ion+lithium ion):citric acid:ethylene glycol=1:1.5:1.5.
[0084] Step 3) to Step 5) are equivalent to Step 3) to Step 5) of Example 1.
[0085] The X-ray diffraction pattern of the lanthanum ion modified lithium-rich manganese-based oxide positive electrode material obtained in Example 3 is as follows: Fig.12 shown.
[0086] According to the same detection method as in Example 1, the results obtained are: at 20 mA g -1 The first cycle activation coulombic efficiency at current density is 82.11% at 100mAg -1 At the current density, after 200 cycles, the discharge capacity retention rate was 72.22%, and the average discharge voltage retention rate was 84.81%. Figure 13 to Figure 15 shown.
[0087] Example 4: A method for preparing a lanthanum ion-modified lithium-rich manganese-based oxide positive electrode material, comprising the following steps:
[0088] 1) The amount of lanthanum nitrate hexahydrate in step 1) of Example 1 was changed from 0.000608 mol to 0.006687 mol, so that the molar ratio of (nickel ion + cobalt ion + manganese ion): lanthanum ion = 90:10;
[0089] The rest is the same as step 1) of Example 1.
[0090] 2) Add 0.242496 mol of citric acid and 0.242496 mol of ethylene glycol to the mixed salt solution obtained in step 1), and mix and stir evenly at room temperature until the citric acid is completely dissolved;
[0091] Therefore, the molar ratio of (nickel ion + cobalt ion + manganese ion + lithium ion + lanthanum ion): citric acid: ethylene glycol = 1:1.5:1.5.
[0092] Step 3) to Step 5) are equivalent to Step 3) to Step 5) of Example 1.
[0093] According to the same detection method as Example 1, the results are as follows: -1 The first cycle activation coulombic efficiency at current density is 83.45%, at 100mAg -1 At the same current density, the discharge capacity retention rate is 81.72% and the average discharge voltage retention rate is 87.53% after 200 cycles.
[0094] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a lanthanum-modified lithium-rich manganese-based oxide positive electrode material, characterized in that The following steps are involved: S1. Add nickel ion salt, cobalt ion salt, manganese ion salt, lithium ion salt and lanthanum ion salt to deionized water, and stir at room temperature until completely dissolved to obtain a mixed salt solution; S2, adding citric acid and ethylene glycol to the mixed salt solution obtained in S1, and uniformly mixing and stirring at room temperature until the citric acid is completely dissolved; S3, placing the solution obtained in S2 in a water bath, and keeping it in a water bath at 60-90°C for 6-24 hours; S4, placing the product obtained in S3 in a vacuum drying oven for constant temperature vacuum drying to obtain a foam precursor; S5. Under air atmosphere, the foam precursor obtained in S4 is subjected to two-step heat treatment in sections to obtain a lanthanum-modified lithium-rich manganese-based oxide positive electrode material.
2. The method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material according to claim 1, characterized in that: In step S1: Nickel ion: cobalt ion: manganese ion: lithium ion = 0.13: 0.12-0.14: 0.53-0.55: (1.15-1.25) × 1.05 molar ratio; The sum of nickel ions, cobalt ions and manganese ions is named transition metal ions, and the molar ratio of transition metal ions: lanthanum ions is 100-x:x, wherein x is 0.1 to 10; The sum of nickel ions, cobalt ions, manganese ions, lithium ions, and lanthanum ions is named as total metal ions; In step S2: The molar ratio of total metal ions: citric acid: ethylene glycol is 1: 0.1-5: 0.1-5.
3. The method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material according to claim 1 or 2, characterized in that: The nickel ion salt, cobalt ion salt, manganese ion salt, lithium ion salt and lanthanum ion salt may be any of the following: nitrate, sulfate, acetate and chloride.
4. The method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material according to claim 3, characterized in that In step S5: The first step of heat treatment is at a temperature of 300 to 700°C, a heating rate of 1 to 7°C / min, and the heat treatment is continued at this temperature for 4.5 to 24 hours; The second step heat treatment temperature is 700-1000°C, the heating rate is 1-7°C / min, and the heat treatment is continued at this temperature for 6-24 hours.
5. The method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material according to claim 4, characterized in that In step S4: The vacuum drying temperature is 100 to 300° C., and the vacuum drying time is 6 to 24 hours.
6. The method for preparing the lanthanum-modified lithium-rich manganese-based oxide positive electrode material according to any one of claims 1 to 5, characterized in that: In step S1: The molar ratio of nickel ion: cobalt ion: manganese ion: lithium ion = 0.13: 0.13: 0.54: (1.2 × 1.05); (nickel ion + cobalt ion + manganese ion): lanthanum ion = 99:1 molar ratio; In step S2: (nickel ion + cobalt ion + manganese ion + lithium ion + lanthanum ion): citric acid: ethylene glycol = 1:1.5:1.5 molar ratio; In step S5: The first step of heat treatment is at a temperature of 500±20°C, a heating rate of 5±0.1°C / min, and the heat treatment is continued at this temperature for 5±0.1 hours; The second heat treatment temperature is 900±20°C, the heating rate is 5±0.1°C / min, and the heat treatment is continued at this temperature for 12±0.1 hours.
7. A method for improving the structural stability of a layered lithium-rich manganese-based oxide positive electrode material for a lithium-ion battery, characterized in that: The material obtained by the method according to any one of claims 1 to 6 is applied to positive electrode materials of lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing lithium-enriched manganese-based anode material of nano-oxide-coated lithium ion battery
CN103441252A
A lithium-rich manganese-based cathode material with a fast-ion conductor coating and a surface heterostructure, and its preparation method.
CN103928664B
Lithium-rich manganese-based positive electrode material with aluminum-doped surface and titanium-aluminum-lithium phosphate-coated surface and preparation thereof
CN111987297A
Sodium / potassium-doped high-performance lithium-rich manganese-nickel-based positive electrode material and preparation method thereof
CN112599765A
Titanium-doped / substituted lithium-rich positive electrode material, and preparation method and application thereof
CN113224290A
